MotifGPL: Motif-Enhanced Graph Prototype Learning for Deciphering Urban Social Segregation - He, Tengfei; Zhou, Xiao (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Social segregation in cities, spanning racial, residential, and income dimensions, is becoming increasingly diverse and severe. As urban spaces and social dynamics grow more complex, residents experience varying levels of segregation, which, if left unaddressed, could exacerbate crime rates, fuel social tensions, and lead to other societal challenges. Effectively addressing these issues requires a comprehensive analysis of the underlying structures of urban spaces and resident interactions. While previous studies have primarily focused on surface-level indicators of segregation, they often fail to explore the complexity of urban structure and mobility dynamics, leaving gaps in understanding modern segregation patterns. To fill this gap, we propose the Motif-Enhanced Graph Prototype Learning (MotifGPL) framework, offering a novel approach to studying urban segregation. The framework consists of three key modules: prototype-based graph structure extraction, motif distribution discovery, and urban graph reconstruction. Specifically, we use prototype-based learning to extract key urban graph prototypes from both spatial and origin-destination graphs, incorporating attributes such as points of interest, street images, and flow indices. The motif distribution discovery module enhances interpretability by matching each prototype to similar motifs, which represent simplified graph structures that reflect local patterns. These motifs are then used to guide the reconstruction of urban graphs, enabling a more detailed exploration of spatial structures and mobility patterns. By identifying critical motifs influencing urban segregation, MotifGPL offers insights to guide the design of urban environments that can help reduce segregation. Experimental results demonstrate that MotifGPL effectively uncovers these key motifs and provides actionable insights for mitigating segregation.